Anonimowe książki polskie z petersburskiej drukarni Krayów – atrybucje i sprostowania - Samborska-Kukuć, Dorota (Acta Universitatis Lodziensis. Folia Librorum, 2013)
In the article the problem of anonymous prints or with wrong authorship printed at the first half of the 19th century in the Kray’s Printing Company in Petersburg is described. The authorship’s issue of Sonety i triolety and so far anonymous works of Onufry Korkozewicz (Poezje, Jadwiga Zborowska, Świętopełk, książę pomorski) is analyzed.